EVALUASI PELAKSANAAN SISTEM PENAGIHAN PAJAK BUMI DAN BANGUNAN DI KANTOR PELAYANAN PAJAK PRATAMA BITUNG - Kamba, Mochammad Eko S.; Saerang, David P.E.; Pusung, Rudy J. (Universitas Sam Ratulangi, 2013)
The success of the ability of the nation itself in increasing the welfare of the people. To improve the well-being of its people, then the necessary funds, one of them through the Earth and building tax. The Earth and building taxes not fully collectible that still lack some of the arrears. To collect the arrears required an exercise of good collection system and organized. Object of the research was conducted at the KPP Pratama Bitung, which retail in this study discusses the evaluation of the implementation of the system of earth and building tax collection at KPP Pratama Bitung. The purpose of the this research is (1) to find out how the implementation of the system of earth and building tax collection at KPP Pratama Bitung, (2) know the level of tax revenues at KPP Pratama Bitung, (3) to find out how well implementation of the Tax collection system at KPP Pratama Bitung. This research uses qualitative data and quantitative data. Analytical method used is descriptive analysis method. The results showed that the implementation of the system of KPP Pratama Bitung in 2009-2011 is already good visible from Earth and building tax receipts that always hit the target set by the Office.